PENGARUH KOMUNIKASI PEMASARAN TERHADAP BRAND IMAGE PRODUK SALONPAS DI ALFAMART CABANG SEPATAN TIMUR - Hermansyah (Program Studi Ilmu Komunikasi, 2025)
Marketing communications has an important role in building the brand image of a product. This research aims to analyze the influence of marketing communications on the brand image of Salonpas products at the East Sepatan branch of Alfamart. The research method used is a quantitative approach by collecting data through questionnaires from 100 Alfamart Sepatan Timur customer respondents who have used Salonpas. The research results show that marketing communication strategies which include advertising, sales promotions and product placement strategies have a significant influence on Salonpas' brand image. These findings provide insight for companies in developing more effective marketing strategies to improve brand perception in the retail market.